Profile of Ocular Trauma in a Tertiary Centre in Western Nepal - Tuladhar, S; Dhakal, S; Poudel, S; Poudel, B (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: Ocular trauma is an important cause of blindness and ocular morbidity throughout the world. The present study was done to establish the common causes of ocular trauma in a Tertiary Care Hospital of Western Nepal.Methods: In this prospective study, all the patients with ocular trauma visiting eye Out Patient Department (OPD) and Emergency Department of Gandaki Medical College Teaching Hospital (GMCTH) from June 2015 to June 2016 were included. A complete history and detailed ophthalmological evaluation was done.Results: Over a period of one year, 226 patients attended to the OPD and Emergency Department of GMCTH. Mean age of patients was 30.41 ±15.7 years. Males were 70.8% and females 29.2%. About 82.5% patients had visual acuity better than 6/18 while 17.7% had visual acuity